2018
DOI: 10.3238/arztebl.2018.0741
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Treatment of Depression in Elderly People in Primary Care

Abstract: epression is one of the commonest mental illnesses affecting persons aged 65 and above (whom we shall call "the elderly" in the rest of this article), with an annual prevalence of 14% (1). Approximately 10% of elderly patients in primary care have depression (2). This highly prevalent condition is clinically significant because it markedly impairs functional ability and quality of life (3), elevates mortality due to suicide (4), and worsens concomitant somatic illnesses (5). Elderly patients with depression su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
(12 reference statements)
1
10
0
Order By: Relevance
“…The control group received treatment as usual (TAU) by GPs. This complex intervention, which was carried out over 1 year, was superior to TAU; 25.6% of the intervention group showed a remission of depressive symptoms compared with 10.9% of TAU (16). This result is comparable with the original US study (17), as well as with other international adaptations (18).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The control group received treatment as usual (TAU) by GPs. This complex intervention, which was carried out over 1 year, was superior to TAU; 25.6% of the intervention group showed a remission of depressive symptoms compared with 10.9% of TAU (16). This result is comparable with the original US study (17), as well as with other international adaptations (18).…”
Section: Introductionsupporting
confidence: 61%
“…After 12 months, the adjusted and estimated remission rate in the intervention group was 25.6% (95% confidence interval, 18.3-32.8), correspondence, 10.9% (5.4-16.5) in the control group (p = 0.004). The detailed study design and the main outcomes are described elsewhere (15,16). The rate of response to treatment was even higher in the intervention group, 22.5% (14.6-30.5) compared with 10.5% (4.1-16.9) in the control group.…”
Section: Study Setting-the Germanimpact Cluster-randomized Controlledmentioning
confidence: 99%
“…All patients gave their written informed consent for study participation prior to the study. A detailed description of the study methods can be found elsewhere [15, 16].…”
Section: Methodsmentioning
confidence: 99%
“…Such a collaborative care approach for late-life depression is the Improving Mood-Promoting Access to Collaborative Treatment (IMPACT) program which has already been proven effective and cost-effective in the USA [13, 14]. The IMPACT program has been recently adapted to the German primary care context and a compatible concept has been developed and proven effective [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…The IMPACT intervention significantly reduced depressive symptoms compared to treatment as usual. A German adaptation, the GermanIMPACT has been conducted as a cluster RCT [41] and yielded significantly positive results concerning depression remission rates compared to treatment as usual [17]. While the participating physicians perceived the program as reducing their workload, the general participation of primary care physicians was low.…”
Section: Psychotherapy In the Context Of Collaborative Care Managementmentioning
confidence: 99%